2005
DOI: 10.3354/ame039225
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous measurement of metabolic activity and membrane integrity in marine bacterioplankton determined by confocal laser-scanning microscopy

Abstract: We simultaneously assessed the metabolic activity and viability of individual bacterioplankton cells in the coastal and open North Sea. Three different techniques were applied to determine cell features related to the physiological status of the cell. SYBR Green I was used to estimate the nucleic acid content of the cell. Propidium iodide (PI) stains cells with a compromised cell membrane, commonly interpreted as indicative of dead cells. Microautoradiography (MA) with radiolabeled glucose and leucine was appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
1

Year Published

2007
2007
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 31 publications
1
13
1
Order By: Relevance
“…In addition, the discrimination of viable cells did not result in a higher correlation with bacterial production (Table 1), as expected from previous reports (Pearce et al 2007, Falcioni et al 2008). Like Pirker et al (2005), our study showed that the PI stain is not the most reliable method of examining bacterial activity in the field. There is still a debate about the estimation of active and viable bacterioplankton, which is in part semantic (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the discrimination of viable cells did not result in a higher correlation with bacterial production (Table 1), as expected from previous reports (Pearce et al 2007, Falcioni et al 2008). Like Pirker et al (2005), our study showed that the PI stain is not the most reliable method of examining bacterial activity in the field. There is still a debate about the estimation of active and viable bacterioplankton, which is in part semantic (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Another easy and helpful technique is nucleic acid double staining (NADS), which is based on simultaneous staining with SYBR Green (staining all cells) and Propidium Iodide (PI, staining only membrane-damaged cells) (Barbesti et al 2000) that allows discrimination of live (PI-impermeable) vs. dead (PI-positive) cells in natural assemblages (Grégori et al 2001, Falcioni et al 2008. Although some authors (Pirker et al 2005) have found that PI-positive cells can also uptake organic substrates, the proportion of viable (PI-impermeable) cells could be considered an acceptable cutoff in the continuum from inactive to active cells.…”
Section: Introductionmentioning
confidence: 99%
“…Particulate phosphate (PartP) was measured using the Strickland and Parsons procedure (1972) for standard DIP, following high-temperature persulfate wet-oxidation at 120 • C and 1 bar (Pujo-Pay and Raimbault, 1994). Sequential filtration was carried out on 1 to 1.2 l samples through different porosity polycarbonate filters (0.2, 0.6, and 2 µm; 47 mm) using Sartorius systems and very low vacuum (drop by drop).…”
Section: Methodsmentioning
confidence: 99%
“…Applying various methods (measurements of the natural abundance of nucleoid-containing cells by combined epifluorescence and phase-contrast microscopy; detection of the reduction of the fluorogenic dye, 5-cyano-2,3-ditolyl tetrazolium chloride; nucleic acid double staining (SYBR Green + propidium iodide); determination of membrane integrity by confocal laser-scanning microscopy), it has been shown that at any given time, a significant fraction of the bacterioplankton community has minimal or no metabolic activity (Zweifel and Hagström, 1995;Sherr et al, 1999;Gregori et al, 2001;Pirker et al, 2005). For this reason, µ estimates based on the HBP:HBB ratio could be underestimated.…”
Section: Growth Rates Estimatesmentioning
confidence: 99%
“…Pirker et al (58) combined microautoradiography and PI to simultaneously assess the metabolic activity and viability of individual bacterioplankton cells in the coastal and open North Sea. In this case, the overwhelming majority (97%) of cells taking up glucose and leucine were also PI positive.…”
mentioning
confidence: 99%